The Role of Social Networking Algorithms in Shaping Jordanian Electronic Public Opinion: Saif Al-Quds Battle as a Model - alkawaldeh, Rozana Nayef Mohammad Nour; AlAlawneh, Hatem Saleem Nhar (Dirasat: Human and Social Sciences, 2024)
Objective: This study aims to assess the awareness of Jordanian users regarding the effects of the algorithmic systems in content management within social media networks, and the strategies they have employed to reduce the impact of algorithms on their pro-Palestinian during the Battle of Saif al-Quds. Methods: This study adopts a descriptive approach, and utilized a survey method. The required data was collected using a questionnaire distributed to (504) Jordanian social media users during the Battle of Saif al-Quds, through the available sample. Results: The younger age groups exhibited a higher level of awareness and knowledge about the existence of targeted algorithms on social media networks and their potential influence and interventions. The results also showed that (49.2%) of the respondents agreed that circumventing the system of algorithms during the publishing process by separating the letters of the words reported in their content using dots and symbols is one of the most effective methods Conclusion: Based on the findings, which suggest an increased awareness among younger Jordanian users about algorithmic interventions, the study recommends investing in the digital literacy of young Jordanians through engaging them in digital security courses. It also suggests designing courses in collaboration with government youth centers in all governorates and for various age groups to enhance digital literacy among certain segments of the Jordanian society.